Evaluation Of The Implementation Of Health Protocol Policies During The Covid-19 Pandemic In Ternate And Tidore Cities: Health Protocol Policies During The Covid-19 Pandemic - Muliana Muliana; Faisal Pataha; Muhamad Sahiddin (STIKes Mandala Waluya Kendari, 2023)
Background : Indonesia first confirmed cases of COVID-19 in March 2020, were 1,528 cases and 136 cases with a mortality rate much higher than that of the People's Republic of China (8.9% vs 4%) Indonesian health facilities are not ready. Objective: To find out the differences in the evaluation model of the Covid 19 health protocol policy in Ternate and Tidore. Methods: Quantitative with a cross sectional study, with a sample of 200 people, data collection through observation and interviews in July-September 2022, and statistical analysis using the Mann Whitney test. Results: The results showed that there were differences in the level of policy implementation from the aspect of resources (p<0.05), bureaucracy (p<0.05) and disposition (p<0.05) in the cities of Ternate and Tidore, but not for the communication aspect (p<0.05). p>0.05). Conclusions: There are differences in the health protocol policy model for the Covid 19 City of Ternate and the City. Suggestions: improve human resource skills and improve the readiness of facilities and infrastructure, SOPs and reporting systems are more structured, it is better to provide standard information delivery procedures and procedures for communication between related agencies, socialization should be carried out more widely and evenly, especially in the islands.